Earthquake scaling and the strength of seismogenic faults - Miller, Stephen Andrew (My University, 2002)
[1] Two important and unresolved issues in tectonics and earthquake mechanics are the strength of seismogenic faults, and scaling relationships between the seismic moment of an earthquake and the area or length of the rupture. These two issues, usually treated separately, are shown here to be fundamentally related. It is shown that the reported scatter in moment-area and moment-length data of strike-slip and dip-slip earthquakes is not scatter, but instead reflects the strength of the fault that failed. Relationships that exhibit continuous scaling between small and large earthquakes are derived, and demonstrate that fault zone pore pressure is the scaling parameter that collapses the combined catalogs of strike-slip and dip-slip earthquakes to a single function. It is shown that for large earthquakes overpressures vary continuously between hydrostatic and near-lithostatic above about 15 km, with evidence for a clear transition to near-lithostatic pore pressures below this depth. These results have significant implications for plate tectonics, earthquake source physics, and mechanistic seismic hazard assessment.